JENIS MAKANAN DAN KETINGGIAN TENGGERAN BURUNG SAAT MEMAKANNYA PADA TIGA TIPE HABITAT DI KAWASAN HUTAN LINDUNG LIANG ANGGANG - BLOK I, BANJARBARU, INDONESIA - Afri Adiyatma Pandian Putra; Mochamad Arief Soendjoto; Eko Rini Indrayatie (Universitas Lambung Mangkurat, 2021)
There are no data on feeding behavior in birds that focus on food types and perch height from ground level while birds eat food. The research aimed to identify the type of food and analyze the height of the perch. Through transects (footpaths, inspection roads) in cultivation crops, settlements, and galam forests in Liang Anggang Protection Forest Area - Block 1, Banjarbaru, Indonesia (KHLLA-1) at 07.00 - 11.00 and at 15.00 - 17.30 and for three replications, birds at a distance of 50 m were observed. The type of food and the height of the perch when the bird ate the food were recorded. Types of food consisted of fruits / seeds, seeds, nectar, insects, fish, and others. Perch height was K-1 for height 0 - <5 m from ground level; K-2 for 5 - <10 m; and K-3 for ≥10 m. One particular bird species that eats certain types of food at certain perch height was called an event. The event ratio was the ratio of certain food types or certain perch height to all events during three replications. Twenty species (14 families) of birds are found to eat and perch. The most dominant type of food eaten is fruit and the least is seeds. Perch height for eating food in general is 0 - <5 m. The number of events at this height is 4.3 - 7.8 times more than the number of events at the height of 5 - <10 m. There is no occurrence that birds eat food at perch height of ≥10 m.Keywords: Bird, Food, Habitat, Perch, Protected Forest